Embolization for the treatment of large, complex fibroids in an outpatient setting: A report of 2 cases - Martyna Czarnik, BA; Frank A. Cusimano, DO, PhD; Sonia Bahlani, MD; Nicole Ciuffo, CST; Adriana Vaglica, RDMS; Christine Mitchell, RVS; Christa Ziffer, RCS; Glenys Hernandez, PAC; Nicole Gentile, RN, BSN; Anthony Watkins, MD; Adam Tonis, DC; David A. Greuner, MD (Radiology Case Reports, 2023)
Uterine leiomyomas are the most common benign pelvic tumors in premenopausal women, causing significant morbidity. Uterine fibroid embolization is a minimally invasive alternative to traditional open or laparoscopic surgeries for the management of symptomatic uterine leiomyoma. For large fibroids, hospitalization after treatment is often required. However, there are limited data on patients with large, complex uterine leiomyomas treated by embolization. This report of 2 cases describes 2 females with large, complex fibroids causing pain and decreased quality of life who were evaluated and treated with embolization in the outpatient setting. Each patient underwent transradial cannulation and uterine artery embolization under local anesthesia or conscious sedation and returned home without complication. For women wishing to preserve their uterus, uterine fibroid embolization is an effective nonsurgical alternative to hysterectomy and myomectomy in an outpatient setting. If standard protocols are followed, embolization by way of transradial artery catheterization is safe for the treatment of large, complex, symptomatic fibroids in the outpatient setting; however, additional studies with larger cohorts are warranted. Accessing the uterine arteries transradially reduces the risk of intra- and post-operative complications for patients, reduces their time spent in a hospital, and minimizes operating costs.